Livability as a public good - Mandishekwa, Robson (Research Journal of Economic and Management Studies, 2021)
Interest in livability of cities has been on the rise for almost four decades. That livability, sustainability and resilience are intertwined is non-debatable. However, the definition of livability still remains marred with difficulties because of seemingly conflicting views. Therefore, it remains less understood among policy-makers and researchers with some perceiving it as quality of life while others perceive it as an environmental quality. This work brings in the views of Charles Tiebout into the livability debate. The objective of this paper is to categorically show that livability is a characteristic of the environment not a quality of life as argued by some authors. The results from the arguments presented show that livability is a public good which enhances life satisfaction and, therefore, quality of life. This corroborates the predictions of the Tiebout model. By so doing, the study managed to show that livability is not quality of life but a person-environment relationship to enhance happiness. Therefore, researchers, planners and policy-makers must understand livability in the context of the person-environment relationship with livability being a public good.